Reliability and validity of the key factors influencing Muslim tourists' behavioural intention in halal tourism to Borneo Island - Nadiah Rus Liyana Rusli; Siti Halimah Putung; Syahrul Nizam Salam; Nordi Achie (Human Resource Management Academic Research Society (HRMARS), 2024)
The purpose of the pilot study is to identify the factors that influence tourist' intentions in halal tourism to the Island of Borneo (Sabah). The population of this study was the Muslim tourists visiting Sabah in 2023. The study used a quantitative research method, employing a purposive questionnaire for the pilot study to 37 local Muslim tourists. Quality, pricing, social factors, Islamic physical attributes, and Islamic non-physical attributes are the independent variables that were analysed using the PLS-SEM: SMART-PLS. This is as well use to determine the significance of the data. However, very limited research focused on religion as the mediator variable that play a significant role in Muslim life. This research was conducted to examine the independent variables, religion as the mediator towards the Muslim behavioural intention. In summary, the study discovered that the visitors' intentions towards halal tourism in Borneo Island (Sabah) could be predicted by Muslim Tourists Perceived Value attributes and religion as the mediator. The pilot survey's findings indicate a strong correlation between Muslim tourists' perceived values of quality, price, social, Islamic physical and non-physical Islamic value with religion, and their behavioural intention to return to the Island of Borneo Sabah. Thus, it shows that the quality, price, social factors, Islamic physical attributes, Islamic non-physical attributes, and religion are important factors influence in revisit intention to Island of Borneo Sabah. The findings indicated that the instrument utilised in this pilot study achieved acceptable reliability and validity levels for the key data collection objectives of the intended research.